Representing Rosalina and Annabel: Filipino Women, Violence, Media Representation, and Contested Realities - Saroca, Cleonicki (Kasarinlan: Philippine Journal of Third World Studies; Vol 22 No 1 (2007): Migration, 2007)
This article examines the relationship between the lives of Filipino women and the images of their abuse that are constructed through several Australian newspapers. It presents case studies of two Filipino women—one a victim of homicide and the other missing in Australia—which are based on a feminist discourse analysis of articles and interviews conducted with their family members and friends. Analyzing newspaper representations vis-à-vis the interviews provides an entirely different, more accurate and just reconstruction of their lives. By charting the lives of these women—their loves and aspirations, and the pain and fear they suffered at the hands of abusive male partners—the article illuminates how newspaper accounts have misrepresented their experiences. Journalists did not account for the domestic violence that was a large part of the women’s lives, and dimensions of their abuse were silenced in the sexist, racist, and class-based discourse of the “mail-order bride.” Such discourse constitutes a sexual and racial “othering” of the women. The media representations reflect a limited understanding of women’s agency and independence within the constraints imposed by their intimate relations. The case studies highlight that the relationship between the media image and actual violence involves conflict over constructions of identity. It is a site of contested realities.
Keywords: Filipino women; domestic violence; “mail-order bride”; media representation; contested realities